Effect of molar intrusion with temporary anchorage devices in patients with anterior open bite: a systematic review - Ahmad Saleem Alsafadi; Mohannad M. Alabdullah; Humam Saltaji; Anas Abdo; Mohamed Youssef (SpringerOpen, 2016)
Abstract Objective The objective of the study is to assess the effect of molar intrusion with temporary anchorage devices on the vertical facial morphology and mandibular rotation during open bite treatment in the permanent dentition. Methods We performed a systematic review of the published data in seven electronic databases up to September 2015. We considered studies for inclusion if they were examining the effects of posterior teeth intrusion on the vertical facial morphology with open bite malocclusion in the permanent dentition. Study selection, risk of bias assessment, and data-extraction were performed in duplicate. Meta-analysis was not possible due to dissimilarity and heterogeneity among the included studies. Results Out of the 42 articles that met the initial eligibility criteria, 12 studies were finally selected. Low level of scientific evidence was identified after risk of bias assessment of the included studies with no relevant randomized controlled trial performed. Out of the 12 selected studies, five studies used miniplates and seven studies used miniscrews. Mandibular counterclockwise rotation was found to be between 2.3° and 3.9° in six studies (as sassed by mandibular plane angle, between MeGo or GoGn and SN or FH plane) while it was less than 2° in the remaining studies. Conclusions Current weak evidence suggests that molar intrusion with temporary anchorage devices may cause mandibular counterclockwise autorotation. Future well-conducted and clearly reported multicenter randomized controlled trials that include a non-treatment control group are needed to make robust recommendations regarding the amount of mandibular rotation during open bite treatments.